Untersuchungen zur Rekonstruktion des Partialdruckes von Kohlendioxid anhand von Coccolithophoridenblüten im Nordatlantik : Biomarker Alkenone und deren Kohlenstoffisotopie - Kirch, Anja (2004)
The dissertation deals with methodological and field studies of alkenones and their carbon isotopes in the North Atlantic (Madeira Basin). The methodological studies focussed on comparison of measurements with gas chromatography with flame ionisation detection and gas chromatography coupled to mass spectrometry. It was possible to separate and detect three C37-, five C38- und five C39-alkenones with a single measurement, even at low concentrations. A goal of the field studies was to determine the original carbon isotope values in alkenones at the time of synthesis during blooms of coccolithophorids. 1)Modifications of this primary delta13C- alkenones-values in the water column were followed up to the sediment traps at 2,000 m and 3,050 m. 2)The values of the underlying sediments were considered. The controversial use of the delta13C-alkenones-values for paleoreconstruction of the partial pressure of carbondioxid was critically examined. Parallel behaviour in the development of temperature and delta13C-alkenones-values were observed for all measured alkenones. Dependencies of different delta13C- alkenones-indices of the temperature were established.